A whale apart: further evidence for genetic isolation of Arabian Sea humpback whales from other recognised subspecies - A. Rita Amaral; Stephen J. Gaughran; Melina I. Giakoumis; Andrew Willson; Gianna Minton; Robert Baldwin; Maia Sarrouf Willson; Suaad Al Harthi; Aida Al Jabri; Tim Collins; Koen Van Waerebeek; Howard C. Rosenbaum (Frontiers in Marine Science, 2026)
Genetic studies have differentiated three subspecies of humpback whales: Megaptera novaeangliae novaeangliae in the North Atlantic, M. n. australis in the Southern Hemisphere and M. n. kuzira in the North Pacific. However, these analyses did not include samples from the Arabian Sea humpback whale population (ASHW). Historic, behavioural, and previously published genetic data suggested that ASHWs are a discrete, isolated and resident population. This study provides further evidence of genetic uniqueness of the ASHWs by comparing samples collected in Oman with the three existing humpback whale subspecies. The morphological and genetic data obtained in this study confirmed the identification of the type specimen for Megaptera indica from Iraq as a humpback whale, closely related to contemporary ASHWs. Genetic differentiation between ASHWs and other subspecies were found (Fst values 0.1213-0.2441 and φ ST values 0.0831-0.6470). Together with the multiple lines of evidence for reproductive and behavioural isolation of this unique humpback whale population that does not undertake seasonal latitudinal migrations as do all other populations, this genetic data support the recognition of a fourth subspecies, which would be named for the type specimen from Iraq: Megaptera novaeangliae indica . Anthropogenic threats to ASHWs and their habitat are severe and escalating and there is a risk of extirpation. Population abundance is low with no evidence of increasing over the past two decades. The genetic differentiation of ASHWs may have been driven by a range of interdependent biogeographical and ecological factors coupled with behavioural adaptations over a period of ~43,000-113,000 years. Regionally coordinated conservation action is urgently needed to preserve this population’s unique genetic diversity.